THE EFFECT OF SP I RITUALITY IN THE WORKPLACE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CULTURE AS INTERVENING VARIABLE AT THE MINISTRY OF RELIGION BULUNGAN DISTRICT - Try Rubianto; Nurul Hidayat; Mestika Sekarwinahyu (STKIP Singkawang, 2021)
The purpose of this study was to examine the effect of workplace spirituality on employee performance at the Ministry of Religion, Bulungan Regency, North Kalimantan with organizational culture as an intervening variable. This research includes research explanatory with population of employee in Unit of the Ministry of Religious Bulungan North Borneo, 140 employees working on including the following: Ministry of Religious Affairs Bulungan District Religious Affairs Office (KUA) Bulungan 10 District and madrasa schools (MAN, MTS, MIN) in Bulungan Regency. This research sample as many as 140 employees. The data analysis technique used in this study uses a path analysis approach. The results showed that the spirituality variable had a positive and significant effect on the employee's work culture. Spirituality variable has a positive and significant effect on employee performance. The work culture variable has a positive and significant effect on employee performance. The work culture variable is able to mediate the influence of spirituality on employee performance.